2008
DOI: 10.1038/sj.bjc.6604424
|View full text |Cite
|
Sign up to set email alerts
|

Fetal growth and the risk of childhood non-CNS solid tumours in Western Australia

Abstract: Using population-based linked health data, we investigated whether the risk of certain childhood non-CNS solid tumours (n ¼ 186) was associated with intra-uterine growth. The risk of retinoblastoma and rhabdomyosarcoma, but not other tumour types, was positively associated with increased growth, suggesting a possible role of fetal growth factors. Larger studies are needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
22
2

Year Published

2009
2009
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 17 publications
1
22
2
Order By: Relevance
“…We and others have not only shown that high birth weight increases the risk of RMS thereby extending the associations reported for childhood cancers, including leukaemia (Caughey and Michels, 2009), brain tumours (Harder et al, 2008) and Wilms tumour (Schuz et al, 2001), but also directly linked it to the extent of growth in utero. Our study supports the view that size for gestational age provides insight beyond that of birth weight per se (Laurvick et al, 2008) and can identify new high-risk groups (Schuz et al, 2001). We observed no association between gestational age and RMS risk, which may also reflect the fact that only 26 embryonal and 7 alveolar RMS cases were born prematurely, spread across 5 weeks before term (32 -36 weeks), whereas only two RMS cases were born very prematurely (more than 5 weeks).…”
Section: Discussionsupporting
confidence: 65%
See 2 more Smart Citations
“…We and others have not only shown that high birth weight increases the risk of RMS thereby extending the associations reported for childhood cancers, including leukaemia (Caughey and Michels, 2009), brain tumours (Harder et al, 2008) and Wilms tumour (Schuz et al, 2001), but also directly linked it to the extent of growth in utero. Our study supports the view that size for gestational age provides insight beyond that of birth weight per se (Laurvick et al, 2008) and can identify new high-risk groups (Schuz et al, 2001). We observed no association between gestational age and RMS risk, which may also reflect the fact that only 26 embryonal and 7 alveolar RMS cases were born prematurely, spread across 5 weeks before term (32 -36 weeks), whereas only two RMS cases were born very prematurely (more than 5 weeks).…”
Section: Discussionsupporting
confidence: 65%
“…This is the first study to show that accelerated in utero growth, measured by higher than expected weight for gestational age, increases the risk of embryonal RMS. The only previous study of relevance suggested an increased risk with increasing birth weight and intrauterine growth (Laurvick et al, 2008), but the small sample size precluded precise estimates. We and others have not only shown that high birth weight increases the risk of RMS thereby extending the associations reported for childhood cancers, including leukaemia (Caughey and Michels, 2009), brain tumours (Harder et al, 2008) and Wilms tumour (Schuz et al, 2001), but also directly linked it to the extent of growth in utero.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An indirect link between imprinting and childhood cancer comes from the association between higher birth weight, accelerated fetal growth, and higher rates of most of the major childhood cancers (17)(18)(19)(20)(21). To the extent that perturbations to imprinting can lead to misregulated growth, this association between growth and cancer may also link misregulated imprinting to cancer.…”
Section: Growth Pathologies: Cancermentioning
confidence: 99%
“…Several studies have looked at various birth characteristics and especially high birth weight has been associated with an increased risk of Wilms tumor with some degree of consistency. [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23] Wilms tumor patients with either Beckwith-Wiedemann syndrome or hemihypertrophy were found to have high birth weights, but a positive association was also seen among children with no other congenital abnormalities. 5 Two studies reported that the association between high birth weight and Wilms tumor was stronger in patients with perilobar nephrogenic rests (PLNR) than in patients with intralobar nephrogenic rests (ILNR), 6,7 whereas the presence of PLNR was associated with loss of imprinting of IGF2, [24][25][26] suggesting that patients with this loss of imprinting account for the birth weight association.…”
mentioning
confidence: 99%